Analysing the Impact of Geopolitical Competition in the Indo-Pacific on the World Order - Dr. Zahid Ullah; Fawad Hussain; Ayub Khan (Dialogue Social Science Review (DSSR), 2025)
This article examines the geopolitical competition between great powers in the Indo-pacific region and its impact on the world order. The Indo-Pacific holds significance because of different sea routes, alternative economic dynamism, potential flashpoints such as Taiwan, the South China Sea, etc., and the pursuit of divergent interests by major powers there. The involvement of great powers—especially their pursuit of divergent policies and the absence of conflict resolution mechanisms—makes the region geo-strategically, geopolitically, and geo-economically significant. The region has thus the potential to shape the emerging international order. Due to its network of strategic maritime outposts, the establishment of military installations, and its increasingly assertive role in the Indo-Pacific, China has positioned itself as a counterweight to the US—the hitherto dominant player in the region. Furthermore, China has shown dissatisfaction with the existing international security and economic arrangements, also known as the liberal world order. The US has declared China and Russia revisionist powers due to their anti-system stances and policies. Therefore, these antagonistic approaches—along with clashing values—to world order manifest in the region in territorial disputes, military competition, and trade wars. Consequently, the global trade and security architecture of the region will be central to the future design of international order. Theoretically, Power transition theory, power differential theory, balance-of-threat theory will be useful theoretical frameworks. Structural Realism—with its focus on lack of cooperation between great powers due to relative gains. The United States, as the dominant power, counters China’s aggressive rise via military alliances like AUKUS and the Quad. Methodologically, the article is based on primary sources (official documents) and secondary sources. This article argues that the geopolitical competition going on in the Indo-Pacific will have profound implications for the existing world order.